Geoscience Rating for Valuation of Exploration Properties - Applicability of the Kilburn Method in Australia and Examples of its Use - Eupene GS (The Australasian Institute of Mining and Metallurgy, 1994)
The valuation of exploration properties which contain no identified resources or reserves is the most subjective of all valuation tasks likely to be carried out by a geologist. The geoscience rating method proposed by Kilburn (1990) recognises this inherent subjectivity but also attempts to apply some discipline to the valuation process. Some other methods used for valuations of this type clearly lack discipline and are open to misuse and abuse. The Kilburn method essentially requires the practitioner to justify all aspects of the valuation process. The valuer must specify and, more importantly, quantify aspects which enhance or downgrade the intrinsic value of each property. The intrinsic value is called the ""base acquisition cost"" (BAC) and it represents the average cost to identify, apply for and retain a base unit of area of title. The BAC and base unit of area both vary with different types of exploration and mining title but remain constant for similar types of titles in the same mineral tenure regime. In the Kilburn Method the enhancement/ downgrading factors are determined by the geotechnical prospectivity (Kilburn Method) within the title. A modified version of the Kilburn Method presented here (""Modified Kilburn Method"") also focuses attention on other real variables besides the geotechnical attributes which influence valuations of this type, viz., competition for tenure and activity in the markets in which the exploration properties are being traded. The most active such market at present is the stock market. By utilising uniform BACs and base units of area (for similar titles) for all exploration properties (in practice in Australia this is only possible within a particular State or Territory), the method exposes the valuer's opinions of each of these variables to the scrutiny of the investor. The investor (or his professional adviser) is afforded the opportunity to directly compare valuations on different properties by different practitioners and can assess how the final valuation is weighted in respect of geotechnical prospectivity, competition for tenure, and stock/financial market sentiment. No other method currently employed in Australia to value mineral exploration properties affords the investor this `luxury', which some may argue is their right.